Kepastian Hukum Pelaksanaan Eksekusi Terhadap Perjanjian Yang Telah Disahkan (Homologasi) - Tedy Herlambang; Nurwidiatmo Nurwidiatmo; Taqiyuddin Kadira (Jurnal Nuansa Kenotariatan, 2017)
This study discusses how the legal certainty and legal protection of the execution of the agreement that has been validated (homologation) between the Respondent Postponement of Obligation of Debt Payment (PODP) to the creditor. Implementation of the execution of homologation between the Respondent for the PODP to the creditors is obtained through Article 170 paragraph 1 of Law Number 37 Year 2004 concerning Bankruptcy and Postponement of Debt Payment Obligation, where if the debtor fails to fulfill the homologation agreement the creditor may demand the cancellation of the treaty, which may make the debtor’s position republished, so that any assets of the debtor may be executed as before any homologation agreement. The execution on the decision used in this study does not materialize for the creditor, because although the debtor has been manifestly and proven to have defaulted against the homologation, the creditor canceling the agreement is not granted by the Panel of Judges.